Royal College of Ophthalmologists' National Ophthalmology Database study of cataract surgery: report 6. The impact of EyeSi virtual reality training on complications rates of cataract surgery performed by first and second year trainees. Issue 3 (29th May 2019) - Ferris, John D; Donachie, Paul H; Johnston, Robert L; Barnes, Beth; Olaitan, Martina; Sparrow, John M
Abstract : Objective: To investigate the impact of EyeSi surgical simulators on posterior capsule rupture (PCR) rates of cataract surgery performed by first and second year trainee surgeons. Design: A Royal College of Ophthalmologists' National Ophthalmology Database audit study of first and second year surgeons' PCR rates over seven consecutive National Health Service (NHS) years. Participating centres were contacted to ascertain the date when their surgeons had access to an EyeSi machine and whether this was on-site or off-site. Operations were classified as before, after or no access to EyeSi. Setting: The study took place in 29 NHS Ophthalmology Units in a secondary care setting. Results: Two-hundred and sixty five first and second year trainee surgeons performed 17 831 cataract operations. 6919 (38.8%) operations were performed before access to an EyeSi, 8648 (48.5%) after access to an EyeSi and 2264 (12.7%) operations by surgeons with no access to an EyeSi. Overall, there was a 38% reduction in the first and second year surgeon's unadjusted PCR rates from 4.2% in 2009 to 2.6% in 2015 for surgeons with access to an EyeSi, and a 3% reduction from 2.9% to 2.8% for surgeons without access to an EyeSi. The overall first and second year unadjusted PCR rates for before, after and no access to EyeSi were 3.5%, 2.6% and 3.8%, respectively. The decrease in the with-access to an EyeSi group PCR rate was similar for surgeons with access to an EyeSi 'on site' or 'off site'. Conclusions: First and second year trainee surgeons' unadjusted PCR rates have decreased since 2009 which has significant benefits for patients undergoing cataract surgery. This 38% reduction in complication rates aligns with the introduction of EyeSi simulator training.